Effectiveness Comparison Between Young Leaf Extracts Acacia nilotica with Desmanthus virgatus Against Vermicidal Potency of Haemonchus contortus In-vitro - I Gusti Komang Oka Wirawan; Aholiab Aoetpah; Jois Moriani Jacob (Jurnal Sain Veteriner, 2021)
Acacia nillotica and Desmanthus virgatus are two entopharmacologycal plants that thrives throughout the season in East Nusa Tenggara Province, other Provinces in Indonesia or tropical countries. Extraction of young leaves of Acacia nillotica (EDMAN) and Desmanthus virgatus (EDMDV) contains tannin compound. By pharmacodynamic viewpoint, this extraction has potency as an anthelmintic. Objective: to compare the in-vitro effectivity of young leaves extraction of the two plants as a vermicidal power to combat Haemonchus contortus. Materials: young leaves of Acacia nillotica and Desmanthus virgatus and Haemonchus contortus. Method: The study was grouped into four treatments: EDMAN, EDMDV, Positive control (Albendazole 0,055%) and negative control (aquades).  The concentration of the young leaves extracts are 2.5%, 3.5%, 4.5% out of 0.01 g/mL of extraction. Each treatment was applied to 6 female Haemonchus contortus with four replicates allowing immersion time for 1, 3, 5 or 7 hours. Variable measured and tested was mortality of the H. contortus. The vermicidal effectively was descriptively analysed. The results showed that mortality percentage (vermicidal) treatment of 2.5%, 3.5%, 4.5% EDMAN for 7-hour immersion was 16.7%, 45.8%, 12.5%, respectively. That values for EDMDV for similar concentrations and immersion time was 50%, 33.3%, 12.5%, respectively. Conclusion: EDMDV has a more effective vermicidal power between the two etnopharmacological treatments at 2.5% concentration.